Occupational and Environmental Exposures and Cancers in Developing Countries - Dana Hashim; Paolo Boffetta (Ubiquity Press, 2014)
Background: Over the past few decades, there has been a decline in cancers attributable to environmental and occupational carcinogens of asbestos, arsenic, and indoor and outdoor air pollution in high-income countries. For low- to middle-income countries (LMICs), however, these exposures are likely to increase as industrialization expands and populations grow. Objective: The aim of this study was to review the evidence on the cancer risks and burdens of selected environmental and occupational exposures in less-developed economies. Findings: A causal association has been established between asbestos exposure and mesotheliomaand lung cancer. For arsenic exposure, there is strong evidence of bladder, skin, lung, liver, and kidney cancer effects. Women are at the highest risk for lung cancer due to indoor air pollution exposure; however, the carcinogenic effect on the risk for cancer in children has not been studied in these countries. Cancer risks associated with ambient air pollution remain the least studied in LMICs, although reported exposures are higher than World Health Organization, European, and US standards. Although some associations between lung cancer and ambient air pollutants have been reported, studies in LMICs are weak or subject to exposure misclassification. For pulmonary cancers, tobacco smoking and respiratory diseases have a positive synergistic effect on cancer risks. Conclusions: A precise quantification of the burden of human cancer attributable to environmental and occupational exposures in LMICs is uncertain. Although the prevalence of carcinogenic exposures has been reported to be high in many such countries, the effects of the exposures have not been studied due to varying country-specific limitations, some of which include lack of resources and government support.